New medical programs as a symbol: between academic legitimacy and market signaling - Fernandez Darraz, Enrique; Bernasconi, Andres (Education Policy Analysis Archives, 2014)
Medical education is complex, highly regulated, and expensive. Why would a university open a medical program? Yet, from 1990 to 2010 medical schools in Chilean universities increased in number from 6 to 28. This growth took place as overall enrolments also expanded four-fold nationally in all fields of higher education, and medical students multiplied by three in the same period. But this expansion of medical education cannot be explained solely on the basis of greater access to higher education and increased demand. An increase in supply was also needed. Why did new medical schools emerge in Chilean universities? Only to create more slots for future MDs? Through the interview-based study reported in this article, we seek to recover the rationale for the creation of medical schools in Chile in the last two decades, and interpret the results according to two theoretical perspectives: the new institutionalism in organizations, and signalling theory. In the recollections of the protagonists of these processes we find evidence both of a quest for academic legitimacy and the intention to provide signals to the market, and a rationale for how these two purposes support one another, as the main benefit foreseen by the promoters of the new medical schools was the improvement of the academic reputation of the university, which in turn would serve to strengthen its competitive position vis á vis other universities.